2000
DOI: 10.1002/1096-9861(20000731)423:3<500::aid-cne12>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin 1 receptor distribution in cholinergic neurons and targets of substance P terminals in the rat nucleus accumbens

Abstract: Substance P (SP) is the major endogenous ligand for neurokinin 1 (NK1) receptors and, together with acetylcholine, has an important role in motivated behaviors involving the limbic shell and motor core of the nucleus accumbens (NAc). To determine the functional sites for SP activation of NK-1 receptors and potential interactions with cholinergic neurons in these regions, the authors examined the electron microscopic immunocytochemical localization either of antisera against the NK1 receptor or of the NK1 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Of three receptors in this class, NK1 are the most abundant and show the highest affinity for substance P (Khawaja and Rogers, 1996;Lu et al, 1998;Saria, 1999). NK1 receptors have been localized to the somatic and dendritic membrane of presumptive cholinergic interneurons immunopositive for the acetylcholine vesicular transporter in rat nACb (Pickel et al, 2000). In that same study, it was also demonstrated that substance P positive terminals make symmetrical synapses with these aspiny neurons.…”
Section: Excitation Of Cholinergic Interneurons: Alternative Mechanismsmentioning
confidence: 85%
“…Of three receptors in this class, NK1 are the most abundant and show the highest affinity for substance P (Khawaja and Rogers, 1996;Lu et al, 1998;Saria, 1999). NK1 receptors have been localized to the somatic and dendritic membrane of presumptive cholinergic interneurons immunopositive for the acetylcholine vesicular transporter in rat nACb (Pickel et al, 2000). In that same study, it was also demonstrated that substance P positive terminals make symmetrical synapses with these aspiny neurons.…”
Section: Excitation Of Cholinergic Interneurons: Alternative Mechanismsmentioning
confidence: 85%
“…It is possible that this reflects developmental differences between our cultures (which are derived from embryonic rats) and adult animals used in previous studies (Pickel et al, 2000; Jabourian et al, 2005). However, we did observe that MORs and NK1Rs are co-expressed in a significant fraction of cultured amygdala neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The antinociceptive effects of morphine remain intact in NK1R knock-out animals, further supporting the specificity of NK1R function in modulating opiate reward (De Felipe et al, 1998). Moreover, MORs and NK1Rs are highly expressed in several brain regions relevant to reward processing, including the ventral striatum and amygdala (Pickel et al, 2000; Gadd et al, 2003; Nakaya et al, 2004; Jabourian et al, 2005; Poulin et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…This antiserum shows a specific band at the predicted 70 kDa molecular weight in Western blots of tissue (Brunelli et al, 2005). The VAChT antiserum has been used extensively in electron microscopy studies in the rat to identify cholinergic processes (Garzón and Pickel, 2000, Pickel et al, 2000, Svingos et al, 2001, Towart et al, 2003, Kaplan et al, 2004). …”
Section: Methodsmentioning
confidence: 99%